2015
DOI: 10.1158/2326-6066.cir-14-0205
|View full text |Cite
|
Sign up to set email alerts
|

Immunity in Head and Neck Cancer

Abstract: Head and neck cancers are a diverse group of malignancies that includes an increasing number of virally mediated cancers in addition to tumors caused by tobacco and alcohol use. In both cases, tumor development is intimately related to the host immune system, and the status of an endogenous antitumor response is likely prognostic. Virally mediated cancers provide unique targets for preventive vaccines that generate immune responses directed against virus-associated antigens. Once head and neck tumors develop, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 45 publications
(49 reference statements)
0
56
0
3
Order By: Relevance
“…Checkpoint inhibitors -e.g., anti-PD-1 antibodies (pembrolizumab and nivolumab), anti-PD-L1 antibody (durvalumab), and anti-CTLA-4 antibody (tremelimumab) -are in active clinical trials and show promising efficacy (6)(7)(8). Although checkpoint inhibitors have clinical activities and improve survival, the benefit extends to only a minority of patients with metastatic and relapsed HNSCC (9,62,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Checkpoint inhibitors -e.g., anti-PD-1 antibodies (pembrolizumab and nivolumab), anti-PD-L1 antibody (durvalumab), and anti-CTLA-4 antibody (tremelimumab) -are in active clinical trials and show promising efficacy (6)(7)(8). Although checkpoint inhibitors have clinical activities and improve survival, the benefit extends to only a minority of patients with metastatic and relapsed HNSCC (9,62,63).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HPV-positive HNSCC patients, which have a more favorable prognosis (3,4), patients with HPV-negative HNSCC have a poor prognosis, with more than half of the patients developing recurrent or metastatic diseases (5). Recently, checkpoint inhibitors, such as mAbs against programmed death-1 receptor (PD-1) and its ligand (PD-L1), have shown promising therapeutic efficacy in both HPV-positive and -negative HNSCC (6)(7)(8). However, these agents confer a benefit in only a minority of patients (9,10), creating a demand to develop new strategies in cancer immunotherapy with defined immunologic mechanisms of action to treat metastatic and recurrent HNSCC tumors.…”
Section: Introductionmentioning
confidence: 99%
“…HNSCC is considered an immunosuppressive disease, characterized by dysregulation of immunocompetent cells and impaired cytokine excretion (15). Immunosuppressive individuals are prone to develop head and neck cancer and prognosis is poor (16). For HPV(-) HNSCC, although there is a strong causative association with tobacco and alcohol, it is hypothesized that tumor progression reflects the inability of the immune system to eliminate the cancer.…”
Section: Immune System and Cancer Developmentmentioning
confidence: 99%
“…HPV infection is common, but a minority of individuals will develop cancer. Failure of the immune system to clear the oncogenic infection accounts for a minority of cases that finally develop cancer; persistence of HPV infection in lymphoid tissue of the head and neck might be related to self-regulatory mechanisms that allow these tissues to sample the oral environment without continuous immune activation (16). Following establishment of HPV infection, HPV specific effector T cells are responsible for elimination of the virus and HPVinduced oncogenesis has been shown to correlate with weak HPV-specific T cell responses (27).…”
Section: Immune System and Cancer Developmentmentioning
confidence: 99%
“…(4) This efficacy highlights the immunogenic nature of SCCHN and supports that immune-based therapies are a rational and promising therapeutic platform for SCCHN. CD8 þ T-cell infiltration has been associated with better overall survival and response to chemoradiotherapy in human papilloma virus (HPV)-positive and HPV-negative patients with locoregionally advanced SCCHN, though this still remains controversial and further studies are needed to confirm these findings (5)(6)(7)(8)(9). Previous work has shown that CD8 þ T-cell enhances the efficacy of radiotherapy through activation of CD8 þ T-cell-mediated cytotoxicity and a decrease in tumor infiltration by myeloid-derived suppressor cells (MDSC; refs.…”
Section: Introductionmentioning
confidence: 99%